An alkaloid fraction extracted from the cactus Trichocereus terscheckii affects fitness in the cactophilic fly Drosophila buzzatii (Diptera: Drosophilidae) - Corio, C. (2013)
The host-plant environment of phytophagous insects directly affects various aspects of an insect's life cycle. Interestingly, relatively few insect groups have specialized in the exploitation of plants in the Cactaceae family, potentially because of the chemical and ecological challenges imposed by these plants. The cactophilic Drosophila buzzatiiPatterson & Wheeler, 1942 is a well-studied model in evolutionary ecology, partially because of its ability to exploit toxic cactus hosts. Previous studies have shown a negative effect on performance when flies are reared in an alternative columnar cactus host of the genus Trichocereus, relative to its primary cactus host, Opuntia. These observations were attributed to the presence of alkaloids in Trichocereus tissues, a chemical deterrent to herbivores that indirectly affects Drosophila larvae; however, the putative toxic effect of alkaloids has never been tested directly in D. buzzatii. The present study is the first attempt to relate chemical extracts in Trichocereus terscheckii Britton & Rose, 1920 with detrimental effects on D. buzzatii. We assessed the effects of a crude alkaloid extract, rich in phenylethylamines, and a 'non-alkaloid fraction' on viability and adult wing morphology. Our results indicate that rearing larvae on an artificial diet containing different concentrations of the crude alkaloid extract decreased pupal viability and adult size in a concentration-dependent manner. We discuss the role of cactus alkaloids in the evolution of host-plant use in cactophilic flies. © 2013 The Linnean Society of London.